Regime type and beyond : the transformation of police in Asia / edited by Weitseng Chen, Hualing Fu. - Chen, Weizeng, 1972-; Fu, Hualing (Cambridge University Press, 2023)
Policing is legitimized in different ways in authoritarian and democratic states. In East and Southeast Asia, different regime types to a greater or lesser extent determine the power of the police and their complex relationship with the rule of law. This volume examines the evolution of the police as a key political institution from a historical perspective and offers comparative insights into the potential of democratic policing and conversely the resilience of authoritarian policing in Asia. The case studies focus on eight jurisdictions: Singapore, Thailand, Hong Kong, Vietnam, China, Taiwan, Japan and South Korea. The theoretical chapters analyse and explain the links between policing and society, the politics of policing and recent police reforms. This volume fills a gap in the literature by exploring the nature of authoritarian policing and how it has transformed and developed the rule of law throughout East and Southeast Asia.